2022
DOI: 10.1021/acscatal.2c00785
|View full text |Cite
|
Sign up to set email alerts
|

Converting CO2 Hydrogenation Products from Paraffins to Olefins: Modification of Zeolite Surface Properties by a UIO-n Membrane

Abstract: In the industry, designing synergetic functional nanocatalysts is a desirable strategy to achieve both high activity and selectivity for CO2 hydrogenation. Herein, we fabricate the bicomponent tandem catalysts ZnZrO x /SAPO-34@UIO-n (n = 66, 66-NH2, and 67) to catalyze CO2 conversion into light olefins. Monodispersed SAPO-34 zeolites are used as the core for the growth of the UIO-n shell to obtain its membrane-encapsulated nanocrystal, SAPO-34@UIO-n, which is mixed by grinding with ZnZrO x to obtain the ZnZrO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Apart from this, HR-TEM and EDS mapping was performed to characterize the morphology and elemental distribution of the catalyst. As shown in Figure 3, Mg-ZnZrO nanoparticle agglomeration (∼50−100 nm with mesopores; see Figure 3a) and only one type of lattice fringe, corresponding to the (011) lattice spacing 26,33,34 of t-ZrO 2 , could be clearly observed. As we can see, the distances between adjacent lattice fringes of Mg-ZnZrO were ∼0.295 nm (Figure 3b) while the distances for ZnZrO were ∼0.289 nm (Figure S4b in the Supporting Information), which evidence that the doping of Mg causes lattice strain in the solid solution lattice.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Apart from this, HR-TEM and EDS mapping was performed to characterize the morphology and elemental distribution of the catalyst. As shown in Figure 3, Mg-ZnZrO nanoparticle agglomeration (∼50−100 nm with mesopores; see Figure 3a) and only one type of lattice fringe, corresponding to the (011) lattice spacing 26,33,34 of t-ZrO 2 , could be clearly observed. As we can see, the distances between adjacent lattice fringes of Mg-ZnZrO were ∼0.295 nm (Figure 3b) while the distances for ZnZrO were ∼0.289 nm (Figure S4b in the Supporting Information), which evidence that the doping of Mg causes lattice strain in the solid solution lattice.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…First, the association between catalytic performance and reaction temperature has been well-researched and the results from 360 °C to 400 °C are shown in Figure b and Table S3 in the Supporting Information. According to thermodynamics, the methanol synthesis (CO 2 + 3H 2 ↔ CH 3 OH + H 2 O, Δ H 298 0 = −45.9 kJ mol –1 ), as well as the RWGS reaction (CO 2 + H 2 ↔ CO + H 2 O, Δ H 298 0 = 42.1 kJ mol –1 ) usually occur at the same time, whereas the latter reaction is more likely to react at high temperature. Thus, the CO 2 conversion improves with the increase of temperature, but the selectivity of undesirable CO byproducts also increases at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that the stable UiO-n membrane passivated the excessive Brønsted acid sites of SAPO-34, suppressing the hydrogenation of olefins to paraffins. Meanwhile, the uniform UiO-66 membrane had no effect on the diffusion step during CO 2 hydrogenation, where the selectivity of the C 2 −C 4 olefins was increased from 57% on ZnZrO x /SAPO-34 to 80% on that with a UiO-66 membrane under 380 °C, 3 MPa, and GHSV of 6000 h –1 (CO 2 /H 2 /Ar = 24:72:4), as shown in Figure 13 a [ 147 ]. Compared with the existing strategies of adjusting the acidity of zeolites by changing the structure of the zeolite framework (e.g., alkali treatment or increasing calcination temperature), the method of membranization by coating a layer of a functional MOF membrane on the zeolite surface did not affect the framework structure.…”
Section: Confined Synthesis and Confinement Effects Of Mofs As Host M...mentioning
confidence: 99%
“… ( a ) The scheme of the ZnZrO x /SAPO-34@MOF catalyst assembly for CO 2 hydrogenation. Reproduced with permission [ 147 ]. Copyright 2022, American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…To address issues resulting from higher aspect ratios of CNTs, several studies have been reported on the synthesis and application of core–shell nanocatalysts. ,,, Gupta et al synthesized a core–shell nanocatalyst with an optimal amount of Fe 3 O 4 and Fe 5 C 2 in the core and partially graphitized carbon in the shell for efficient CO 2 hydrogenation . Fe 3 O 4 nanoparticles encapsulated inside graphitic carbon shells (Fe 3 O 4 @carbon) have been found to be more efficient than conventional catalysts. , Porous graphene-confined Fe–K was found to be a highly efficient catalyst for direct CO 2 hydrogenation to light olefins .…”
Section: Introductionmentioning
confidence: 99%